UDMURT INSTITUTE OF HISTORY, LANGUAGEAND LITERATURE UrB OF THE RAS: TIME OF ANALISIS - Zagrebin, A.E. (Perm Federal Research Centre Journal, 2014)
The article is devoted to the history of Udmurt Institute of History, Language and Literature of the Ural Branch of the RAS. Since the 1920s, the process of national-state construction among Finno-Ugric peoples of Russia was in need of scientific foundation of the legislation and administrative decisions. Questions related to management, determination of boundaries of the autonomies, language policy and relationships between various groups of population became the interest sphere of historians, ethnographers, folklorists and linguists. Due to cooperation of science and politics, the researchers were supposed to search for a delicate balance between practices that reflect mosaic picture of native life, and biased texts of official reports. The inclusion of the Institute into academic infrastructure liberated scientists from many bureaucratic conventions, at the same time preserving a number of rituals and directions of activity, which link the Institute with local authorities.